Peran Pembiayaan Syariah Dalam Mendukung Kelangsungan Usaha Mikro Kecil (Umk) Di Indonesia : Studi Fenomenologi - Putri, Oktaria Ardika (WADIAH, 2025)
This study aims to explore the role of Islamic financing in supporting the sustainability of Micro and Small Enterprises (MSEs) in Indonesia. This research uses a qualitative approach with a phenomenological method. Data was collected through in-depth interviews with ten MSE actors who are customers of Islamic banks in Kediri Regency. The results show that Islamic financing plays a role not only as a source of business capital but also as a means of spiritual peace for Muslim entrepreneurs. The principles of profit-sharing (mudhārabah and musyārakah) are considered more equitable, although they require a more complex process. Non-financial support such as business assistance and religious guidance from the bank strengthens this relationship. This research implies the need for increased financial literacy and simplification of sharia financing products to be more accessible to MSEs.